The Big Five Personality dengan Minat Beli Gamis pada Mahasiswi yang dimoderatori oleh Persepsi terhadap Kualitas Produk - Arga Prasetiya; Ratri Kurnia Ihsani; M. Luhung Pribadi (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to find out the relationship between the big five personality with the buying interest of the robe, which moderated by the perception of the product quality at Ahmad Dahlan University Yogyakarta students. A total of 65 students from Ahmad Dahlan University in Yogyakarta from various faculties and any major. The data collection of the research sample was carried out by a cluster sampling technique. This research using the big five personality inventory (BFI), the scale of perception of product quality, and the scale of buying interest. Research data analysis was performed by analysis using path analysis techniques. The results showed a negative relationship between the big five personality and buying interest which was moderated by the perception of the product at Ahmad Dahlan University Yogyakarta students. The path of analysis coefficient shows the total impact of p = -0.10. The total impact is smaller than the direct impact of the big five personality with buying interest which shows the path analysis coefficient of p = 0.07. These results indicate that the perception of product quality as a moderator variable has a negative impact on the relationship between the big five personality and buying interest. Based on the results of the study, the hypothesis proposed in the study was rejected.